Peran Kinerja Pegawai dan Kepemimpinan dalam Meningkatkan Kualitas Pelayanan Publik Studi pada Dinas Penanaman Modal dan PTSP Kota Solok - Afni Yeni; Nurhayati Nurhayati; Fitri Suriani (JURNAL ADMINISTRASI KANTOR, 2025)
The following study aims to provide knowledge on employee performance and leadership style towards service quality at the Investment and PTSP Office of Solok City. The study category used is a quantitative approach with a total sampling technique, where the entire population consisting of 37 employees is used as a sample. Data were collected using a questionnaire. The technique for analyzing the data obtained is multiple linear regression analysis showing that employee performance and leadership style have an effect on service quality, t-test, and f-test. The results of this study note that: (1) employee performance has a significant impact on the independent variables at the Investment Model and PTSP Office of Solok City; (2) service quality has a significant impact on the independent variables at the Investment Model and PTSP Office of Solok City; and (3) leadership style and dependent variables have a significant and simultaneous impact on the independent variables at the Investment Model and PTSP Office of Solok City. In addition, the coefficient of determination test was 54.9%, then the remaining 45.1% was factored into other variables not included in this study, for example work experience, job rotation, and job satisfaction. Keywords: Employee Performance, Leadership Style, Service Quality